CUSTOMER'S PERCEPTION AND DIGITALIZAION ABLE TO INCREASING INTEREST TO INVEST IN GOLD IN ISLAMIC SHCEME - Marcella Nazmatul Lail (Veteran Economics, Management, & Accounting Review, 2024)
The aim of this research is to find and determine the influence of perceptions of Islamic banking products, digitalization and income on interest in investing in gold at BSI Mobile. Sampling used purposive sampling technique with a total sample of 121 respondents. The approach used is a quantitative model with data collection techniques using questionnaires. SPSS 26 and Excel are data analysis tools. Data testing uses data quality tests, classical assumption tests, multiple linear regression analysis tests and hypothesis tests. The results of this research are that perceptions of sharia banking products and digitalization partially have a significant effect on interest in investing in gold at BSI Mobile, while partially income does not significantly affect interest in investing in gold at BSI Mobile. Simultaneously, all independent variables have a significant effect on the dependent variable.